Reoperation Rates following Single-Level Discectomy. Issue 1 (April 2016) - Heindel, Patrick; Tuchman, Alexader; Hsieh, Patrick; Pham, Martin; Patel, Neil; Jakoi, Andre; Liu, John; Buser, Zorica; Wang, Jeffrey C.
Introduction: Lumbar discectomy is the most commonly performed procedure for treatment of radiculopathy due to lumbar disc herniation. Randomized trials have demonstrated the advantage of surgical removal of herniated disc material over non-surgical treatment options, allowing for a more rapid reduction in symptoms and return of function. Many small-size studies suggest that long-term outcomes for patients treated with discectomy and non-operative management are similar. Additionally, treatment of recurrent lumbar disc herniation is not standardized. Population-level data regarding reoperation following single level hemilaminotomy and discectomy is limited. Material and Methods: Data was collected and analyzed for 13, 654 patients undergoing single-level lumbar discectomy between January 2007 and December 2010 using the commercially available PearlDiver software (PearlDiver, Inc., Fort Wayne, IN, USA). The nationwide Humana private insurance database was queried for patients billed with the Current Procedural Terminology (CPT) code for our index procedure, hemilaminotomy and removal of disc material (CPT-63030). Patients receiving concurrent lumbar surgeries were excluded from the index group. The index group was then followed in retrospective cohorts for 3 months, 6 months, 1 year, 2 years, and 4 years for recurrent lumbar surgery, including spinal fusion, laminectomy, and additional discectomy. Results: Patients received additional lumbar surgeries following single-level discectomy at a rate of 3.95% (539/13654) within 3 months and 12.2% (766/6274) within 4 years of the index procedure. Lumbar spinal fusion was performed on 5.90% (370/6274) of patients within 4 years, with interbody fusion in 75.4% (279/370) of cases and multi-level fusion in 47.0% (174/370) of cases. Reoperation for re-exploration discectomy at the same level as the index procedure with no subsequent surgeries occurred in 2.71% (170/6274) of patients followed out to 4 years. Patients who received a re-exploration discectomy at the same intervertebral level within 2 years of the index procedure went on to receive lumbar fusion at a rate of 38.4% (48/125) within the 4 years following the re-exploration discectomy. Conclusion: Data in our study demonstrated a reoperation rate of 12.2% after single level discectomy, a routinely performed procedure for the treatment of symptomatic lumbar disk herniation. Moreover, we show that the rate of progression to lumbar fusion after a re-exploration discectomy was 38.4% within 4 years of reoperation. These data should help surgeons in their operative decision-making and counseling recommendations to patients. To our knowledge, this is the largest population study delineating reoperation rates across the US after single-level lumbar discectomy. Further studies are needed regarding the best treatment algorithm in patients with re-herniation or iatrogenic instability following lumbar discectomy.